Endoscopic Transnasal Resection of Midline Skull Base Meningiomas: Tumor Consistency and Surgical Outcomes - Al Abdulsalam, Hissah K.; Aldahish, Aljohara K.; Albakr, Abdulrahman; Hussain, Sajjad; Alroqi, Ahmad; Alromaih, Saud; Alsaleh, Saad; Ajlan, Abdulrazag M. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Background The endoscopic transnasal approach (ETA) has proven to be of great value in the resection of midline skull base meningiomas when compared with traditional approaches. Our objective was to assess tumor consistency in relation to surgical outcomes for midline meningiomas (MMs) resected using ETA.Methods Radiological preoperative features, including the tumor to cerebellar peduncle T2-weighted magnetic resonance imaging (MRI) ratio (TCTI), were evaluated. The intraoperative consistency assessment was performed by the surgeon, which determined if the tumor was soft (resectable by suction) or firm (required a cavitation ultrasonic aspirator). Surgical resection and postoperative complications were evaluated in relation to tumor consistency.Results Twenty patients were evaluated; 6 were classified as firm and 14 were classified as soft. The mean TCTI ratio was 1.7 and the median was 1.7 (range: 1.3–2.4). Three firm tumors had a ratio of <1.6. All soft tumors had a ratio of ≥1.6 with three outliers. Additionally, 66.7% of patients with firm tumors had complications compared with 35.7% of patients with soft tumors. Only 33.3% of firm tumors underwent gross total resection (GTR) in comparison to 79.0% of tumors with a soft consistency.Conclusion In our analysis, we found that tumor consistency was significantly related to short-term surgical outcomes in MMs resected using the ETA. The TCTI ratio was found to be the most reliable predictor with a sensitivity of 76.9% and a specificity of 40.0%. Our findings suggest that traditional cranial approaches should be considered as the first surgical option for managing firm MMs.
Keywords: meningioma; tumor consistency; magnetic resonance imaging; surgical outcome